Additive manufacturing of a nickel–aluminium–bronze alloy via directed energy deposition - Li, Boyuan (Nanyang Technological University, 2023)
Nickel–aluminium–bronze (NAB) alloys have been substantially utilised in aerospace, marine, and offshore applications due to their excellent mechanical performance and corrosion resistance. Directed energy deposition (DED) is a disruptive metal additive manufacturing (AM) technology, which enables high design freedom and enormous flexibility in fabricating parts of complex geometries. However, the printability, microstructure, and performance of NAB alloys manufactured by DED have received little attention. This Ph.D. thesis focuses on the process–microstructure–property relationship of NAB alloys prepared by DED and the effects of thermal cycles on the homogeneity of printed components. DED was utilized to fabricate an NAB alloy with a hierarchical microstructure and ultrahigh mechanical strength. The process was optimized to print near-fully dense NAB parts. The hierarchical microstructure consisted of multi-scale microstructural features, including microscale cellular structures, sub-microscale crystallographic grains, and nanoscale deformation twins and precipitates. The deposited NAB contains a martensite β* phase with Fe3Al precipitates and a Widmanstätten α phase with NiAl precipitates. The synergistic effect of these hierarchical features contributes toward superior mechanical strength and good ductility. The yield strength (YS) of the printed NAB alloy reached 593–713 MPa, which was 160% higher than that of the cast counterpart. The highest ultimate tensile strength (UTS) reached 950 MPa while the elongation was maintained at 10–12%. The underlying strengthening mechanisms include grain refinement strengthening, dislocation strengthening, precipitation strengthening, and solid solution strengthening. A strategy to manipulate the thermal history of the DED process is proposed to eliminate the heterogeneity of the NAB alloy, since the thermal history has significant effects on the microstructure and properties of printed parts. Severe heat accumulation occurred during printing, as heat conduction was suppressed within the as-built component as the building height increased. In air-cooled (AC) NAB samples, the microstructure and mechanical properties significantly varied across the printed sample due to changing cooling rates at different layers. This thesis employs water cooling (WC) to eliminate the heterogeneity of the microstructure and mechanical properties induced by the heat accumulation. Meanwhile, the faster cooling rate also contributes to higher tensile strength. The YS of WC samples was higher than that of AC samples by 119.75%, 93.22%, and 39.73%, at the top, middle, and bottom positions, respectively. The significance of thermal manipulation on the process control, microstructure modification, geometrical design, and printing strategy design was analysed incisively. An NAB/15-5 PH steel multimaterial was fabricated via DED, yielding a combination of outstanding mechanical performance and excellent corrosion resistance. A defect-free NAB/15-5 PH interface was achieved, at which an interlayer of FexAl dendrites formed. These interfacial characteristics were induced by a synthetic effect of liquid phase separation, Marangoni convection, and atom diffusion. The 15-5 PH solidified prior to NAB and formed intermetallic dendrites. FexAl clusters were produced in the NAB region due to Marangoni convection in the melt pool. The UTS of multimaterial samples was 754.64 and 854.57 MPa in the transverse and longitudinal directions, respectively. Along the transverse direction, plastic deformation accumulated more in the NAB region than in the 15-5 PH region, because of the lower YS of the NAB alloy. Tensile cracks initiated along the interface of FexAl/Cu due to the incoherence between the FexAl dendrites and Cu matrix. Along the longitudinal direction, brittle FexAl dendrites constrained the deformation, thus, resulting in an early failure. This Ph.D. thesis establishes the process–microstructure–property relationship of the NAB alloy fabricated by DED, develops a thermal manipulation approach to eliminate the heterogeneity of the NAB alloy, and reveals the enormous potential of DED for fabricating NAB-containing multimaterials.